Comparison Of Oral Iron and Iv Iron Sucrose for Treatment of Anemia in Postpartum Indian Women - Aggarwal Rohina S; Mishra Vineet V; Panchal Navin A; Patel Nital H; Deshchougule Vrushali V; Jasani Anil F (Medsci Publications, 2012)
Objectives: To determine the efficacy of intravenous iron sucrose and oral iron in anaemic postpartum women, presenting at Institute of Kidney Disease and Research Centre. Method: Descriptive case series. The study was carried out in the department of Obstetrics and Gynaecology at Institute of Kidney Disease and Research Centre over a period of six months from 02- 02-2010 to 02-08-2010. 50 cases with proven iron deficiency with Hb ≤7gm% were included in the study. Total iron deficit was calculated using a standard formula. Target haemoglobin was 12 gm %. Iron sucrose was administered by intravenous infusion. Haemoglobin was repeated 1, 2, 3, and 4 weeks after the last dose of intravenous iron sucrose. Results: On inclusion, the 2 groups were comparable in terms of both anthropometric and biologic data Distribution of cases by economic status showed, 21 patients (42.0%) belonged to lower class, 20 patients (40%) belonged to middle class and 09 patients (18%) were of upper class).Target hemoglobin levels were achieved in 4 weeks' time in 20 (80%) patients in iron sucrose group as compared to 10 (40%) of patients in oral iron group .There was significant improvement in the various hematological parameters in iv sucrose group as compared to patients in oral iron group. There were no significant allergic reactions in IV sucrose group. Conclusion: This study has shown a significant improvement in the iron sucrose group. Iron sucrose is safe and well tolerated.